The Chinese Sultanate: Islam, Ethnicity, and the Panthay Rebellion in Southwest China, 1856-1873 by David G. Atwill (Stanford, CA: Stanford University Press, 2005. 264 pages.) (American Journal of Islam and Society, 2006)
David G. Atwill’s recent historical work joins in the anthropological streamof studying the ethnic groups of China’s Yunnan province. This book presentsa history of the violence in nineteenth-century Yunnan, to which ethnicity,economics, culture, environment, and politics all contributed. It consistsof ten chapters, the first of which discusses the bloody history of the Hui(Muslim) genocide by the Han (Chinese). In this chapter, Atwill identifieswhy the Han resent the Hui and refutes conventional assumptions about thePanthay rebellion (1856-72). The second chapter situates nineteenth-centuryYunnan in mosaic landscapes of region, commerce, ethnicity, and geographyand provides the context for understanding the ensuing violence. The thirdchapter presents the history, communities, and networks of Muslims inmultiethnic Yunnan, and the fourth chapter discusses Han trouble-makers(Hanjianism) in Yunnan’s borderlands and presents a history of non-Hanresistance to Han expansion.The fifth and sixth chapters concentrate on Han hostility toward the Huiand documents in detail the massacre of Muslims by Han officials and militiaas well as major Hui resistance campaigns: rebellions in Yunnan’s eastern,southern, and western regions. The seventh chapter discusses divisionsamong Yunnan’s Hui, which were largely due to differences in region, religion,and personal ambitions, along with the Qing policy of using some Huito control other Hui. The eighth chapter focuses on the Dali regime (1856-72), which Atwill surprisingly labels as “Sultanate,” and discusses its multiethniccharacter. The ninth chapter presents the back-and-forth battlesbetween the Dali Sultanate and the Qing, and the fall of the Dali regime. Thetenth chapter, as an epilogue, critiques the existing scholarship, which failsto note the facts of the Han massacre of the Hui and the multiethnic backingof the Dali regime. It also restates that the Panthay rebellion was primarilya Hui-led indigenous multiethnic resistance to the Han immigrants’ hunger ...